2014
DOI: 10.1590/0103-8478cr20131167
|View full text |Cite
|
Sign up to set email alerts
|

Serology for brucellosis in free-ranging crab-eating foxes (Cerdocyon thous) and brown-nosed coatis (Nasua nasua) from Brazilian Pantanal

Abstract: Serology for brucellosis in free-ranging crab-eating foxes (Cerdocyon thous) and brown-nosed coatis (Nasua nasua)... Ciência Rural, v.44, n.12, dez, 2014. 2193Serology for brucellosis in free-ranging crab-eating foxes (Cerdocyon thous) and brown-nosed coatis (Nasua nasua) from Brazilian Pantanal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…in the crab-eating foxes. In contrast, Dorneles et al (2014) diagnosed the B. abortus infection in five C. thous, while Hayashi (2013) performed PCR in 41 crab-eating foxes from Parque Nacional da Emas region, Brazil, but did not find any positive sample for Brucella sp. These negative results for Brucella sp.…”
Section: Discussionmentioning
confidence: 91%
“…in the crab-eating foxes. In contrast, Dorneles et al (2014) diagnosed the B. abortus infection in five C. thous, while Hayashi (2013) performed PCR in 41 crab-eating foxes from Parque Nacional da Emas region, Brazil, but did not find any positive sample for Brucella sp. These negative results for Brucella sp.…”
Section: Discussionmentioning
confidence: 91%
“…In the Pantanal wetland, B. abortus has already been identified in crab-eating foxes (Cerdocyon thous), brown-nosed coatis (Nasua nasua), and pampas deer (Ozotoceros bezoarticus) [25,26], and its occurrence in cattle was reported [23,24]. Thus, the contact of dogs with wildlife and cattle may promote the transmission of B. abortus among them, as was reported in Egypt [20].…”
Section: Discussionmentioning
confidence: 93%
“…With approximately 160,000 ha in the core of South America, this region shelters a rich and dense wild mammalian fauna that shares the same habitat with domestic animals [22]. Cases of brucellosis caused by B. abortus have been reported in the Pantanal region that affect some species of domestic animals Responsible Editor: Miliane Souza and wildlife [23][24][25][26][27]. Although Furtado et al (2015) [27] previously reported that dogs are exposed to Brucella spp.…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea, Brucella DNA was found in blood (1/9) and tissues (2/5) of introduced raccoons (172). Three (8.8%) of 34 brown-nosed coatis ( Nasua nasua ), which also belong to family Procyonidae, were serologically positive for Brucella in the Brazilian Pantanal (149).…”
Section: Bartonella and Brucella Infections In Wild Carnivores By Familymentioning
confidence: 99%